Pengaruh Biaya Operasional Terhadap Laba Bersih UMKM Kopikir Coffee di Kota Malang - Nina Imroatul Chasanah (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to identify whether there is an impact of operational costs on the net profit of Kopikir Coffee shops. This research is included in the category of quantitative research. The research was carried out at the Kopikir Coffee shop on Sudimoro Street, Lowokwaru District, Malang, East Java. The population of this study is all monthly financial statements of Kopikir Coffee. The number of research samples is 48 data, with data criteria that present complete monthly financial statements for the 2019-2023 period. The data used in this study comes from secondary sources in the form of monthly financial statements owned by Kopikir Coffee. The data collection mechanism applied in this analysis involves literature study, observation, and documentation. The data analysis method applied in this study is a simple linear regression model. Based on the results of the hypothesis test, operational costs have an influence and a negative relationship on net profit. The operational costs carried out in Kopikir Coffee store activities are high so that the achievement of profits will decrease. So the result of this research is that operational costs have an effect and are significant on the net profit of the Kopikir Coffee shop. Keywords: Operational Costs, Net Profit